TRANSFORMATIONAL LEADER DETERMINATION, COMPETENCE AND ORGANIZATIONAL CLIMATE WITH WORK SATISFACTION AS INTERVENING VARIABLES TO PERFORMANCE ENVIRONMENTAL SERVICE EMPLOYEES BINTAN DISTRICT - Handriyanto, Handriyanto; Rumengan, Jemmy; Rumengan, Angelina Eleonora (Universitas Batam, 2019)
In this study, researchers used respondents' data, such as gender, age and duration of work of respondents to be able to provide information about the characteristics of respondents. Where from the questionnaire distributed questionnaire as many as 60 respondents using census techniques. The results of the study are as follows: The effect of the X3 variable on X4 has a P-Values value of 0.005 <0.05, so it can be stated that the influence between X3 and X4 is significant. The effect of the X3 variable on Y has a P-Values value of 0,000> 0.05, so it can be stated that the effect of X3 on Y is significant. The effect of the X4 variable on Y has a P-Values value of 0.009> 0.05, so it can be stated that the effect between X4 on Y is significant. The influence of X1 on X4 has a P-Values value of 0.006 <0.05, so it can be stated that the influence between X1 to X4 is significant. The influence of X1 on Y has a P-Values value of 0.031> 0.05, so it can be stated that the effect between X1 on Y is significant. The effect of the X2 variable on X4 has a P-Values value of 0.001 <0.05, so it can be stated that the effect between X2 on X4 is significant. The effect of X2 on Y has a P-Values value of 0.045 <0.05, so it can be stated that the effect between X2 on Y is significant.